2016
DOI: 10.21614/chirurgia.111.5.439
|View full text |Cite
|
Sign up to set email alerts
|

Patient Specific Instruments for Complex Tumor Resection-Reconstruction Surgery within the Pelvis: A Series of 4 Cases

Abstract: The pelvis bone resection-reconstruction surgery is one of the most challenging fields in orthopedics. Being applied for tumors, as for other complex reconstruction cases, this type of surgery needs careful planning and is time consuming, in order to obtain proper accuracy. Unfortunately not all the time the expected accuracy is met, with consequences for the patients. PSI proved to provide good cutting accuracy during simulated tumor surgery within the pelvis. This article present a series of 4 patients opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
(3 reference statements)
1
15
0
Order By: Relevance
“…In our series, pathological margins were negative after bone tumor resection. According to previous studies, the mean operative duration and intraoperative blood loss ranged from 258-445 min and 2206-6210 ml, respectively [7,11,19,21,22,32,36]. In the current study, the mean operative duration and intraoperative blood loss were reduced to 333 min and 1416 ml, respectively.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In our series, pathological margins were negative after bone tumor resection. According to previous studies, the mean operative duration and intraoperative blood loss ranged from 258-445 min and 2206-6210 ml, respectively [7,11,19,21,22,32,36]. In the current study, the mean operative duration and intraoperative blood loss were reduced to 333 min and 1416 ml, respectively.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, the cost is another great disadvantage of surgical navigation system [35]. Gerant et al [36] reported that major blood loss occurred during osteotomy. Osteotomy guide plates can help surgeons perform multiplanar osteotomy, achieve precise resection margins, shorten the operative duration and reduce intraoperative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the standard of care for RCC, with minimally invasive partial nephrectomy the treatment of choice for localized lesions [ 561 ]. PubMed Search: (3D printing AND kidney cancer) OR (rapid prototyping and kidney cancer) OR (3D printing AND renal cancer) OR (rapid prototyping AND renal cancer) OR (3D printing AND renal mass) OR (3D printing AND kidney mass) OR (rapid prototyping AND renal mass) OR (rapid prototyping AND kidney mass) OR (3D printing AND renal cell carcinoma) OR (3D printing AND RCC) OR (rapid prototyping AND renal cell carcinoma) OR (rapid prototyping AND RCC) Results: [ 308 , 310 324 ] The terms renal lymphoma, angiomyolipoma (AML) and renal oncocytoma generated no results when searched with 3D printing or rapid prototyping. Renal Cysts : Renal cysts are common; they are heterogeneous in both origin and pathogenesis; and most are simple and are usually of little clinical significance.…”
Section: Appendixmentioning
confidence: 99%
“…PubMed Search: (3D printing AND pediatric genitourinary tumor) OR (rapid prototyping AND pediatric genitourinary tumor) OR (3D printing AND Wilms tumor) OR (rapid prototyping AND Wilms tumor) OR (3D printing AND nephroblastoma) OR (rapid prototyping AND nephroblastoma) Results: None Relevant Musculoskeletal (Retrieved February 2017) Fracture : Simple, Acute Complex Long Bone, Acute Complex Intraarticular, Complex, Acetabular, Non-Pathological Vertebral, Pathological Vertebral, Fracture Malunion. PubMed Search: ((“printing, three-dimensional”[MeSH Terms] OR (“printing”[All Fields] AND “three-dimensional”[All Fields]) OR “three-dimensional printing”[All Fields] OR (“3d”[All Fields] AND “printing”[All Fields]) OR “3d printing”[All Fields]) OR (rapid[All Fields] AND prototyping[All Fields])) AND ((“fractures, bone”[MeSH Terms] OR (“fractures”[All Fields] AND “bone”[All Fields]) OR “bone fractures”[All Fields] OR “fracture”[All Fields]) OR malunion[All Fields]) Results: [ 345 – 406 ] Heterotopic Ossification PubMed Search: ((“printing, three-dimensional”[MeSH Terms] OR (“printing”[All Fields] AND “three-dimensional”[All Fields]) OR “three-dimensional printing”[All Fields] OR (“3d”[All Fields] AND “printing”[All Fields]) OR “3d printing”[All Fields]) OR (rapid[All Fields] AND prototyping[All Fields])) AND (“ossification, heterotopic”[MeSH Terms] OR (“ossification”[All Fields] AND “heterotopic”[All Fields]) OR “heterotopic ossification”[All Fields] OR (“heterotopic”[All Fields] AND “ossification”[All Fields])) Results: None relevant Ligamentous Injury PubMed Search: ((“printing, three-dimensional”[MeSH Terms] OR (“printing”[All Fields] AND “three-dimensional”[All Fields]) OR “three-dimensional printing”[All Fields] OR (“3d”[All Fields] AND “printing”[All Fields]) OR “3d printing”[All Fields]) OR (rapid[All Fields] AND prototyping[All Fields])) AND ((“tendons”[MeSH Terms] OR “tendons”[All Fields] OR “tendon”[All Fields]) OR (“ligaments”[MeSH Terms] OR “ligaments”[All Fields] OR “ligament”[All Fields])) Results: [ 407 , 408 ] Hip Dysplasia PubMed Search: ((“printing, three-dimensional”[MeSH Terms] OR (“printing”[All Fields] AND “three-dimensional”[All Fields]) OR “three-dimensional printing”[All Fields] OR (“3d”[All Fields] AND “printing”[All Fields]) OR “3d printing”[All Fields]) OR (rapid[All Fields] AND prototyping[All Fields])) AND (“hip dislocation”[MeSH Terms] OR (“hip”[All Fields] AND “dislocation”[All Fields]) OR “hip dislocation”[All Fields] OR (“hip”[All Fields] AND “dysplasia”[All Fields]) OR “hip dysplasia”[All Fields]) Results: [ 389 , 409 414 ] Bone or Soft Tissues Neoplasm: With or Without Joint and Neurovascular Involvement PubMed Search: ((“printing, three-dimensional”[MeSH Terms] OR (“printing”[All Fields] AND “three-dimensional”[All Fields]) OR “three-dimensional printing”[All Fields] OR (“3d”[All Fields] AND “printing”[All Fields]) OR “3d printing”[All Fields]) OR (rapid[All Fields] AND prototyping[All Fields])) AND (“bone neoplasms”[MeSH Terms] OR (“bone”[All Fields] AND “neoplasms”[All Fields]) OR “bone neoplasms”[All Fields] OR (“bone”[All Fields] AND “tumor”[All Fields]) OR “bone tumor”[All Fields]) Results: [ 324 , 353 , 415 443 ] Arthritis, Not Otherwise Specified PubMed Search: (...…”
Section: Appendixmentioning
confidence: 99%
“…PSI cutting guides are valuable for tumour resection in the pelvis, allowing for accurate resection margins, graft sizing, opposition and, hence, improving the stability of the reconstructed pelvis [ 22 ] where complex, multi-faceted cuts are sometimes used in conjunction with custom-made endoprostheses. In a series of nine patients with 11 osteotomies reported by Gouin [ 23 ] for pelvic tumour resection, placement of PSI guides was usually straightforward in the pelvis with an accuracy of within 2.5 mm.…”
Section: Three-dimensionally Printed Patient-specific Tools and Guidementioning
confidence: 99%